Policy Analysis of Subscription Parking on Public Roadside After the Issuance of Medan Mayor Regulation Number 26 of 2024 - Tuah Damanik, Harlen; Revida , Erika; Reza, Muhammad; Gunawan Siregar, Ace Indra (PT ARRUS Intelektual Indonesia, 2024)
he purpose of this study is to understand the policy analysis of subscription parking on public roadside after the issuance of Medan Mayor Regulation Number 26 of 2024. The research method used a qualitative method by conducting direct observation, conducting interviews, and collecting data in the form of documents, and library research or data obtained from other sources, such as books and news media. The implementation of subscription parking services in Medan City can be indicated as a trial policy and a symptom of public service failure. This indicates that the organization of subscription parking service providers has not been able to coordinate well, the obligations and responsibilities of service providers have not been able to be implemented properly, the rights of users of subscription parking services have not been able to be fulfilled in their entirety, the perception and response of users to subscription parking services are not satisfactory.